Does The Privatization Worth It? Factors Influencing the Quality of the Brazilian Privatization (British Journal of Multidisciplinary and Advanced Studies, 2023)
The state's economic participation has been intensely debated over the past three decades. In Brazil, especially after the advent of the Federal Constitution of 1988. Privatization in Brazil, however, was instituted by Law 8.130/90, which instituted the National Privatization Plan, aiming to transfer to the private sector activities improperly exploited by the public sector. This article investigates the quality of services provided by privatized companies or public concessions through interviews. The main conclusions indicated a complex privatization process, as there is evidence related to five topics: (i) oversight, (ii) quality in privatization, (iii) regulation, (iv) competition, and (v) public service. In addition, the careful analysis suggested implications for the privatization process and public concessions. In addition, implications for the public administration to focus its efforts on improving oversight and scheduling itself in pre-regulating the privatization process. Finally, free competition aimed at competitiveness and low prices are topics to be discussed in this article.